iPhone and iPad Apps for Absolute Beginners - Lewis, Rory.; Moroney, Laurence; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
This update of an Apress bestseller walks you through creating your first app, with plain English and practical examples using the latest iOS 7 software development platform and more. It cuts through the fog of jargon and misinformation that surrounds iPhone and iPad app development, and gives you simple, step-by-step instructions to get you started. Teaches iPhone and iPad apps development in language anyone can understand Provides simple, step-by-step examples that make learning easy, using iOS 7 Offers bonus videos from the author that enable you to follow along$1 (Bit$1 (Bs like your own private classroom The iPhone is the hottest gadget of our generation, and much of its success has been fueled by the App Store, Apple$1 (Bs online marketplace for iPhone apps. Over 1 billion apps were downloaded during the nine months following the launch of the App Store, ranging from the simplest games to the most complex business apps. Everyone has an idea for the next best-selling iPhone app$1 (Bthat$1 (Bs why you$1 (Bre reading this now! And with the popularity of the iPad, this demand will just continue to grow.s
Keywords: Computer science; Computer Science; Computer Science, general